Ascetic figure with a long beard on the pillar - Temples of India Project Team (Jio Institute, 2024)
The ascetic is shown on one of the pillars with a long beard and what seems like a jata. A kamandala is tied to one of his shoulders through a rope. He wears nothing but a kopina/loin cloth and the sacred thread janeyu, shown quite prominently. Janeyu reminds us that the lineage of ascetics in the Pashupata sect has been predominantly Brahmins, right from the time of Lakulisha and his four disciples and even Lakulisha has been elsewhere depicted in this temple with a prominent janeyu. The bare minimum clothing and kamandalu are signifiers of his asceticism.